The Evaluation on the Effectiveness of eSAFER Form as Hazard and Near Miss Reporting Method - Mohd Fauzi, Noor Adzirah; A.Razak, Aliff Hisyam; Mahfodz, Rozaidi (Progress in Engineering Application and Technology, 2023)
Safety, health, and welfare of workers is priority at any industry. There are lot of hazards and near miss reporting method in a variety of industry. One of the methods is by using See and Fix Error Report (SAFER) Card. Besides, SAFER Card gives the awareness about unsafe condition and unsafe act that can cause hazard and near miss at the workplace and workstation. SAFER Card used as a report card to report if there any hazard or near miss at the workplace. A new method of hazard and near miss reporting by using digital platform was introduce and was named as eSAFER Form. The reason why new method was implemented is because inconsistent hazard and near miss reporting in monthly basis was recorded using the SAFER Card. The implementation of this new method starts with propose the idea if this new method to the management team to get their approval. Once the proposal has been accepted, briefing and implementation of the new method continued. All employees involved in the briefing to ensure they aware with the new method of hazard and near miss reporting. The data after a month of implementation this method was collected to analysed to know the effectiveness of the new method. From the data analysis, it shows an improvement after applying eSAFER Form. Only one department not showing too much improvement compared to before implement eSAFER Form. Another department show an impress improvement by increasing higher than the target set. Furthermore, the department that not achieved target before implement eSAFER Form has reached the target and even exceed the target set. This shows good feedback after implement eSAFER Form and this also shows that most department feel comfort to use the new method compare the old method. In addition, average for the targeted hazard and near miss report is 32 reports need to be submitted by monthly in a year. Meanwhile, hazard and near miss report after implement eSAFER Form is 43 reports in a month. This can be concluded that using eSAFER Form as a new method to report hazard and near miss at workplace was effective. However, it would be better if data can be collected and analysed for a long time of period and a better system could be implement for this new method.